Association between SCAP and SREBF1 gene polymorphisms and metabolic syndrome in schizophrenia patients treated with atypical antipsychotics. (17th August 2016) - Yang, Lin; Chen, Jianhua; Li, Yan; Wang, Yan; Liang, Shiqiao; Shi, Yongyong; Shi, Shenxun; Xu, Yifeng
Abstract: Objectives : The use of atypical antipsychotics (AAPs) in the treatment of schizophrenia has been relevant because of the high prevalence of metabolic syndrome (MetS). The sterol-regulatory element-binding protein (SREBP) pathway may contribute to the underlying pathophysiology of AAP-induced metabolic adverse effects. We explored the association between the variants of the sterol-regulatory element-binding transcription factor-1 ( SREBF1 ) gene and the SREBP cleavage-activation protein ( SCAP ) gene with AAP-induced MetS in a genetic case–control study.Methods : Eleven single nucleotide polymorphisms (SNPs) of SREBF1 and five of SCAP were genotyped in a Han Chinese population in Beijing, China: a sample of 722 schizophrenia patients on monotherapy with AAPs (clozapine, olanzapine or risperidone). Metabolic parameters were collected and evaluated for MetS criteria.Results : The rs11654081 T-allele of the SREBF1 gene was significantly associated with an increased risk for MetS after correction ( P  = 0.019, odds ratio, OR =2.56, 95% confidence interval, CI: 1.4 4–4.54). The rs11654081-TT genotype appeared more frequently in MetS than in non-MetS after correction ( P  = 0.026, OR =2.37, 95% CI: 1.3 6–4.12). SCAP polymorphisms with drug-induced MetS were negative in this study.Conclusions : The genetic polymorphisms of SREBF1 could play a role in the mechanism for interindividual variation of AAP-induced MetS.